Mutation of an L-Type Calcium Channel Gene Leads to T Lymphocyte Dysfunction - Fenninger, Franz; Han, Jeffrey; Stanwood, Shawna R.; Nohara, Lilian L.; Arora, Hitesh; Choi, Kyung Bok; Munro, Lonna; Pfeifer, Cheryl G.; Shanina, Iryna; Horwitz, Marc S.; Jefferies, Wilfred A. (Frontiers in Immunology, 2019)
Calcium (Ca2+) is a vital secondary messenger in T lymphocytes regulating a vast array of important events including maturation, homeostasis, activation, and apoptosis and can enter the cell through CRAC, TRP, and CaV channels. Here we describe a mutation in the L-type Ca2+ channel CaV1.4 leading to T lymphocyte dysfunction, including several hallmarks of immunological exhaustion. CaV1.4-deficient mice exhibited an expansion of central and effector memory T lymphocytes, and an upregulation of inhibitory receptors on several T cell subsets. Moreover, the sustained elevated levels of activation markers on B lymphocytes suggest that they are in a chronic state of activation. Functionally, T lymphocytes exhibited a reduced store-operated Ca2+ flux compared to wild-type controls. Finally, herpes virus infection demonstrates that the parts of the phenotype of the CaV1.4-deficient mice is aggravated by environmental factors. This is the first example where the mutation of a CaV channel leads to T lymphocyte dysfunction, including the upregulation of several inhibitory receptors, hallmarks of T-cell exhaustion and establishes the physiological importance of CaV channels signalling in maintaining a nimble immune system.